TECHNOLOGY DEVELOPMENT OF COMPUTER EXPERT SYSTEM IN BUSINESS PLANNING - Shorikov, A.F.; Butsenko, E.V.; Krylov, V.G. (Perm Federal Research Centre Journal, 2016)
The article deals with the topical issues of development of expert systems for the implementation of business planning process.